Central and haematopoietic interleukin-1 both contribute to ischaemic brain injury in mice - Adam Denes; Fiona Wilkinson; Brian Bigger; Michael Chu; Nancy J. Rothwell; Stuart M. Allan (The Company of Biologists, 2013)
SUMMARY Interleukin-1 (IL-1) is a key regulator of inflammation and ischaemic brain injury, but the contribution of central and peripheral sources of IL-1 to brain injury is not well understood. Here we show that haematopoietic-derived IL-1 is a key driver of ischaemic brain injury. Wild type (WT) mice transplanted with IL-1αβ-deficient bone marrow displayed a significant (40%) reduction in brain injury induced by focal cerebral ischaemia compared with WT mice transplanted with WT bone marrow. This was paralleled by improved neurological outcome and the almost complete absence of splenic-derived, but not liver-derived, IL-1α after stroke in WT mice lacking haematopoietic-derived IL-1. IL-1αβ knockout (KO) mice transplanted with IL-1αβ-deficient bone marrow showed a 60% reduction in brain injury compared with WT mice receiving WT bone marrow. Transplantation of WT bone marrow in IL-1αβ KO mice resulted in a similar level of blood-brain-barrier injury to that observed in WT mice receiving IL-1αβ-deficient bone marrow. Cerebral oedema after brain injury was reduced in IL-1αβ KO recipients irrespective of donor-derived IL-1, but a lack of haematopoetic IL-1 has also been associated with smaller brain oedema independently of recipient status. Thus, both central and haematopoietic-derived IL-1 are important contributors to brain injury after cerebral ischaemia. Identification of the cellular sources of IL-1 in the periphery could allow targeted interventions at these sites.